2016
DOI: 10.1108/ijopm-01-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Leanness assessment: a literature review

Abstract: Purpose Assessing the outcome of lean transformation journey has been of interest to both researchers and practitioners. Various qualitative and quantitative assessment methodologies have been proposed in literature to track and measure the degree of leanness attained. The purpose of this paper is to understand the evolution of this leanness assessment literature over different attributes and identify gaps for future research. Design/methodology/approach A detailed literature review of peer-reviewed journal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
125
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(140 citation statements)
references
References 73 publications
10
125
1
4
Order By: Relevance
“…Moreover, this type of representation allows benchmarking with other organizations. Thus, the membership function associated with each fuzzy aggregate Lean Index, LI ij , should be transformed into a crisp value by using the defuzification method mentioned in the last section, which is based on equation (12), (13) and (14). Then, the values obtained for each criterion are represented in Figure 5.…”
Section: Case Study -Application Of the Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this type of representation allows benchmarking with other organizations. Thus, the membership function associated with each fuzzy aggregate Lean Index, LI ij , should be transformed into a crisp value by using the defuzification method mentioned in the last section, which is based on equation (12), (13) and (14). Then, the values obtained for each criterion are represented in Figure 5.…”
Section: Case Study -Application Of the Proposed Methodsmentioning
confidence: 99%
“…However, the approach proposed in this paper follows the trend of lean thinking assessment literature, which is getting transformed from process-level monitoring to enterprise-level monitoring [14]. The recently published material about leanness assessment revealed that future studies in this domain would fall into two major categories, namely manufacturing leanness assessment and service leanness assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Publications in this field have increased considerably with an increasing number of industries trying to adopt this philosophy of work in its productive processes [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the approach proposed in this paper follows the trend of lean thinking assessment literature, which is getting transformed from process-level monitoring to enterprise-level monitoring [27]. The recently published material about leanness assessment revealed that future studies in this domain would fall into two major categories, namely manufacturing leanness assessment and service leanness assessment.…”
Section: Some Backgroundmentioning
confidence: 99%